mRNA-based dendritic cell immunization improves survival in ret transgenic mouse melanoma model - Sharbi Yunger, Adi; Grees, Mareike; Utikal, Jochen; Umansky, Viktor (OncoImmunology, 2016)
Malignant melanoma is characterized by a rapid progression, metastasis to distant organs and resistance to chemo and radiotherapy. Although melanoma is capable of eliciting an immune response, the disease progresses and the overall results of immunotherapeutic clinical studies are not satisfactory. Recently, we have developed a novel genetic platform for improving an induction of peptide-specific CD8+ T cells by dendritic cell (DC) based on membrane-anchored β2-microglobulin (β2m) linked to a selected antigenic peptide at the N-terminus and to the cytosolic domain of TLR4 at the C-terminus. In vitro transcribed mRNA transfection of antigen-presenting cells (APCs) resulted in an efficient coupling of peptide presentation and cell activation. In this research, we utilize the chimeric platform to induce an immune response in ret transgenic mice that spontaneously develop malignant skin melanoma and to examine its effect on the overall survival of tumor-bearing mice. Following immunization with chimeric construct system, we observe a significantly prolonged survival of tumor-bearing mice as compared to the control group. Moreover, we see elevations in the frequency of CD62LhiCD44hi central and CD62LloCD44hi effector memory CD8+ T-cell subsets. Importantly, we do not observe any changes in frequencies of regulatory T cells (Tregs) and myeloid-derived suppressor cells (MDSCs) in the vaccinated groups. Our data suggest that this novel vaccination approach could be efficiently applied for the immunotherapy of malignant melanoma.
Gesehen am 23.10.2019